AN ANALYSIS OF METAPHOR IN ONE DIRECTION ALBUM - Agustin, Tuti Dwi; Tanduklangi, Amri; Sapan, Yulius Tandi (Universitas Halu Oleo, 2019)
Lyrics in song are intended to send a message to the audience or music lovers. Composers use figurative language as the media to convey their message. One of the figurative languages that is mostly used in song’s lyrics is Metaphor. This study was intended to investigate the types of metaphor used in One Direction Album. The objective of this study to identify the types of metaphor found in the song lyrics and to analyze metaphor meaning in One Direction song. This study adopted a descriptive qualitative research design. Three songs by One Direction had been chosen as the data of this study; Story of My Life, Steal My Girl and Drag Me Down. The data were analyzed its metaphor by using Lakoff and Johnson theory, while in investigating the meaning, Chaer’s theory of contextual meaning was used. The result of the study showed that based on the three types of metaphor, structural metaphor becomes the most frequently used in the song lyrics, meanwhile 2 of 3 songs used all of the three types of metaphor; Orientation, Structural and Ontological Metaphor. In answering the second research question about the meaning of each metaphor, each lyric has been analyzed through content analysis to know the true meaning of what the song writer want to express in his/her lyrics and each lyric has different contextual meaning which is elaborated further in this study. Keywords: Metaphor, Meaning, One Direction’s Album